2022
DOI: 10.1111/ahg.12493
|View full text |Cite
|
Sign up to set email alerts
|

NLRP13 inflammasome complex is hypermethylated in familial Mediterranean fever and global methylation correlates with the disease severity

Abstract: Familial Mediterranean fever (FMF) is an autoinflammatory disease caused by variations in the MEFV gene, which encodes the pyrin protein, a member of the inflammasomes. Despite the complex pathogenesis of FMF, epigenetic changes also play roles in the disease progression. In our previous study, we observed a relationship between NLRP13, which is one of the members of the inflammasome complex and has a pyrin domain in its structure, and the MEFV gene using the STRING database. In this study, we examined NLRP13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The discrepancy between low expression of ZEB1 and ZEB2 in PRAD samples, as indicated by gene expression analyses, and their high expression as revealed by IHC. It has been reported that microRNAs such as miR-203, miR-200a, miR-525-5p, miR-127, miR-101-3p and miR-186-5p play a role in the EMT pathway by downregulated ZEB1 and ZEB2 in various cancers including gastric, breast, and colorectal [31,32]. Despite this, the intricacies of post-transcriptional regulation, involving factors like microRNAs and RNA stability, have the potential to influence protein synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The discrepancy between low expression of ZEB1 and ZEB2 in PRAD samples, as indicated by gene expression analyses, and their high expression as revealed by IHC. It has been reported that microRNAs such as miR-203, miR-200a, miR-525-5p, miR-127, miR-101-3p and miR-186-5p play a role in the EMT pathway by downregulated ZEB1 and ZEB2 in various cancers including gastric, breast, and colorectal [31,32]. Despite this, the intricacies of post-transcriptional regulation, involving factors like microRNAs and RNA stability, have the potential to influence protein synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the presence of amyloidosis was associated with hypermethylation of the NRLP13 gene, hence resulting in its silencing and subsequently in the inhibition of inflammasome assembly. This discovery unveiled a new epigenetic mechanism contributing to the development of FMF [ 40 ]. The NLRP3 inflammasome was also found to be significantly demethylated in monocytes derived from FMF patients and associated with increased expression of IL-1β [ 41 ].…”
Section: Dna Methylationmentioning
confidence: 99%
“… 29 It has never been assessed if the IL-1-enrichment in FMF patients affects the epigenetic programming of monocytes specifically, although a recent study found that global DNA methylation is correlated with disease severity. 30 This indicates a more detailed epigenetic investigation is warranted in FMF.…”
Section: Introductionmentioning
confidence: 99%